Populocracy : the tyranny of authenticity and the rise of populism - Fieschi, Catherine, 1967- (Comparative political economy., 2019)
"Catherine Fieschi examines why populism and populist parties have become a feature of our politics. Populism's appeal, she argues, needs to be understood as a response to the fundamental reshaping of our political, economic and social spheres through globalisation and the digital revolution"--